Influence of Supplier Relationship Management on Product Quality - Carter, Dr. Emily (International Journal of Supply Chain Management, 2024)
Purpose: The aim of the study was to analyze the influence of supplier relationship management on product quality. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low-cost advantage as compared to field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: effective Supplier Relationship Management (SRM) practices, such as performance monitoring, collaboration, and trust-building, significantly enhance product quality. These practices reduce defect rates, improve compliance, and boost customer satisfaction. Strong supplier relationships foster innovation, align quality objectives, and streamline processes, making SRM a critical enabler for achieving consistent quality standards and maintaining competitive advantage in dynamic markets. Unique Contribution to Theory, Practice and Policy: Resource-Based View (RBV), Transaction Cost Economics (TCE) Theory and Stakeholder Theory in supply chain and management maybe used to anchor future studies influence of supplier relationship management on product quality. Theories should incorporate variables such as cultural, technological, and economic differences, providing a more globally relevant understanding of SRM's influence on product quality. Firms should adapt SRM practices to their industry-specific needs. For instance, green supply chains might prioritize sustainability metrics, while high-tech sectors may emphasize innovation partnerships. Policymakers should promote industry-wide standards for supplier evaluations and quality compliance to ensure consistency and accountability across supply chains